Electrode active material and preparation method thereof, and preparation method of carbon-coated lithium manganese iron phosphate
Through the preparation of manganese iron phosphate iron ivory materials, mixing the use of iron source and hydrochloric acid solution is mixed with different additives to synthesize and high temperature synthesis, solving the problem of uneven distribution of elements, preparing high chemical performance and electrochemical performance The porous structure is a solid -soluble electrode activity material.
Patent Information
- Application Number
- CN202411480050.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-22
AI Technical Summary
The existing lithium manganese iron phosphate positive electrode material has the problem of uneven element distribution during the preparation process, resulting in local area manganese or iron enrichment, causing phase separation and crystal structure distortion, thereby reducing lithium ion transmission rate, rate performance and Cyclic performance.
By mixing an iron source and a hydrochloric acid solution, adding different additives and then performing atomization and high-temperature synthesis, a uniform solid solution electrode active material with a porous structure is prepared. The method involves using Additive 1 (containing manganese source), Additive 2 (containing manganese source, phosphoric acid and reducing agent) or Additive 3 (containing manganese source, phosphorus source, lithium source and reducing agent) to ensure an even distribution of each element.
The prepared electrode active material has a uniform element distribution, avoids phase separation, improves the chemical and electrochemical properties of the material, and meets the practical application requirements of lithium-ion batteries.
Smart Images

Figure CN119349534A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrode materials, and in particular relates to an electrode active material and a preparation method thereof, and a preparation method of carbon-coated lithium manganese iron phosphate. Background Art
[0002] Lithium-ion batteries have the advantages of high energy density, long cycle life, and no memory effect. They are widely used in electronic products, electric transportation, energy storage and other fields. The main cathode materials of lithium-ion batteries are lithium cobalt oxide, lithium manganese oxide, nickel cobalt manganese (ternary) system, lithium iron phosphate, lithium manganese iron phosphate and so on. With the application of lithium-ion batteries, commercial products have higher and higher requirements for the cost performance of lithium-ion batteries, which is mainly reflected in the increasingly fierce competition among battery factories for the cost per watt-hour of batteries. In recent years, the market share of lithium iron phosphate has surpassed that of ternary batteries, on the one hand because lithium iron phosphate is safer, and on the other hand because the price of lithium iron phosphate is lower. Lithium manganese iron phosphate is a co-solvent of lithium manganese phosphate and lithium iron phosphate. It has high safety and stability similar to lithium iron phosphate, and has a higher platform voltage and energy density. Its operating voltage (4.1V) is 20% higher than that of lithium iron phosphate (3.4V), and its theoretical energy density is about 20% higher than that of lithium iron phosphate. The theoretical cost of lithium manganese iron phosphate batteries is lower than that of lithium iron phosphate, so the research on lithium manganese iron phosphate by the material side, battery side and vehicle manufacturers has gradually deepened. It is considered to be the most promising next-generation lithium-ion power battery positive electrode material.
[0003] The synthesis methods of lithium iron manganese phosphate are mainly divided into solid phase method and liquid phase method. The solid phase method uses mixed sintering of manganese source, iron source, phosphorus source and lithium source. It has the advantages of simple process, less equipment required, easy production and low cost, and is widely used in the preparation of lithium iron manganese phosphate positive electrode materials. The liquid phase method mainly includes sol-gel method, solvent thermal method, hydrothermal method, spray drying method, etc. Taking the sol-gel method as an example, this method dissolves the phosphorus source, manganese source (manganese nitrate), iron source (ferric nitrate) and lithium source in a certain proportion, crystallizes to obtain liquid slurry, preheats to form a honeycomb gel, and obtains the finished lithium iron manganese phosphate through crushing, rolling, sintering and grinding.
[0004] However, the lithium manganese iron phosphate cathode materials commercially prepared by the existing solid-phase method and liquid-phase method are not uniform solid solutions, and there is a problem of uneven distribution of phosphorus, iron and manganese elements, which leads to manganese enrichment or iron enrichment in local areas, causing phase separation and exacerbating the Mn 3+ The Jahn-Teller effect and cooperative elastic deformation of ions accelerate the distortion of the crystal structure, resulting in a rapid decrease in lithium ion transfer rate, rate performance, gram capacity and cycle performance, making it difficult for its comprehensive electrochemical performance to meet the requirements of practical applications, thus restricting the commercial application of lithium manganese iron phosphate materials. Summary of the invention
[0005] The object of the present invention is to provide an electrode active material and a preparation method thereof, and a preparation method of carbon-coated lithium manganese iron phosphate. The electrode active material prepared by the method provided by the present invention is a uniform solid solution with a porous structure, and the elements in the material are evenly distributed, which improves the consistency of the quality of the active material and thereby improves the electrochemical performance of the lithium manganese iron phosphate product.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] The present invention provides a method for preparing an electrode active material, comprising the following steps:
[0008] mixing an iron source and a hydrochloric acid solution to obtain an iron source solution;
[0009] Mixing the iron source solution and the additive to obtain a mixed solution;
[0010] The mixed solution is sequentially subjected to atomization and high-temperature synthesis to obtain the electrode active material;
[0011] The additive includes additive 1, additive 2 or additive 3;
[0012] The additive 1 includes a manganese source;
[0013] The additive 2 includes a manganese source, phosphoric acid and a reducing agent;
[0014] The additive 3 includes a manganese source, a phosphorus source, a lithium source and a reducing agent.
[0015] Preferably, the iron source includes one or more of Fe, FeO, Fe2O3, Fe3O4, FeCl2, FeCl3, FeCO3, FeC2O4 and FeOOH;
[0016] The iron source solution contains H + The concentration is 4-12 mol / L;
[0017] In terms of the amount of iron, the Fe element and H in the iron source solution + The amount of substance ratio is 1:2~8.
[0018] Preferably, the manganese source includes one or more of Mn, MnO, MnCl2, MnCO3 and MnC2O4;
[0019] The phosphorus source includes one or more of phosphoric acid, lithium phosphate and lithium dihydrogen phosphate;
[0020] The lithium source includes one or more of lithium carbonate, lithium hydroxide, lithium chloride, lithium phosphate and lithium dihydrogen phosphate.
[0021] Preferably, when the additive is additive 1, the concentration of manganese and iron ions in the mixed solution is 60 to 300 g / L, wherein Mn 2+ The amount of substance of accounts for 0.1 to 1 of the amount of substance of manganese and iron ions, and is not 1;
[0022] When the additive is additive 2, the concentration of manganese and iron ions in the mixed solution is 60-300 g / L; 2+ The amount of substance of accounts for 0.1 to 1 of the amount of substance of manganese and iron ions, and is not 1; based on the amount of substance of phosphorus element, the ratio of the total amount of substance of manganese and iron ions to the amount of substance of phosphorus element is 0.95 to 1.0:1;
[0023] When the additive is additive 3, the concentration of manganese and iron ions in the mixed solution is 60-300 g / L; 2+ The amount of substance accounts for 0.1 to 1 of the amount of substance of manganese iron ions, and is not 1; based on the amount of substance of phosphorus element and lithium element, the ratio of the total amount of manganese iron ions to the amount of substance of phosphorus element is 0.95 to 1.0:1, and the ratio of the amount of substance of lithium element and phosphorus element is 0.95 to 1.05:1.
[0024] Preferably, the reducing agent comprises one or more of citric acid, oxalic acid, tartaric acid, formic acid and hydroxylamine hydrochloride;
[0025] The mass of the reducing agent is 1-5% of the mass of the electrode active material.
[0026] Preferably, the atomization method is gas-liquid two-fluid atomization; the gas pressure of the atomization is 0.3-0.8 MPa, and the average particle size of the mist droplets obtained by the atomization is 10-100 μm.
[0027] Preferably, when the additive is additive 1, the temperature of the high temperature synthesis is 500 to 1000° C., and the holding time is 10 to 60 seconds;
[0028] When the additive is additive 2, the temperature of the high temperature synthesis is 500 to 800° C., and the holding time is 10 to 60 seconds;
[0029] When the additive is additive 3, the temperature of the high temperature synthesis is 600-900° C., and the holding time is 10-60 seconds.
[0030] The present invention also provides an electrode active material prepared by the preparation method described in the above technical solution. When the additive is additive 1, the electrode active material is recorded as electrode active material 1. The electrode active material 1 is manganese iron oxide. The chemical composition of the manganese iron oxide is (Mn x Fe 1-x)2O3, where 0.1≤x<1;
[0031] When the additive is additive 2, the electrode active material is recorded as electrode active material 2, the electrode active material 2 is ferromanganese pyrophosphate, and the chemical composition of the ferromanganese pyrophosphate is (Mn x Fe 1-x )2P2O7, where 0.1≤x<1;
[0032] When the additive is additive 3, the electrode active material is recorded as electrode active material 3, the electrode active material 3 is lithium iron manganese phosphate, and the chemical composition of the lithium iron manganese phosphate is LiMn x Fe 1-x PO4, where 0.1≤x<1;
[0033] The electrode active material has a porous structure.
[0034] The present invention also provides a method for preparing carbon-coated lithium manganese iron phosphate, comprising the following steps:
[0035] Providing an electrode active material, wherein the electrode active material is the electrode active material described in the above technical solution;
[0036] Carbon-coating the electrode active material to obtain the carbon-coated lithium manganese iron phosphate;
[0037] When the electrode active material is the electrode active material 1, the carbon coating process is: mixing the electrode active material 1, lithium dihydrogen phosphate and a carbon source, and calcining;
[0038] When the electrode active material is electrode active material 2, the carbon coating process is: mixing electrode active material 2, a lithium source and a carbon source, and calcining; the lithium source includes lithium carbonate or lithium hydroxide;
[0039] When the electrode active material is the electrode active material 3, the carbon coating process is: mixing the electrode active material 3 and the carbon source, and calcining.
[0040] Preferably, the calcination temperature is 500-900° C., and the holding time is 3-20 hours.
[0041] The present invention provides a method for preparing an electrode active material, comprising the following steps: mixing an iron source and a hydrochloric acid solution to obtain an iron source solution; mixing the iron source solution and an additive to obtain a mixed solution; atomizing and high-temperature synthesizing the mixed solution in sequence to obtain the electrode active material; the additive comprises additive 1, additive 2 or additive 3; the additive 1 comprises a manganese source; the additive 2 comprises a manganese source, phosphoric acid and a reducing agent; the additive 3 comprises a manganese source, a phosphorus source, a lithium source and a reducing agent.
[0042] The advantages of the present invention are:
[0043] 1. The obtained active material is a homogeneous solid solution with uniform distribution of elements, which avoids phase separation of positive electrode materials and ensures that the product has high chemical properties;
[0044] 2. The obtained active material has a porous structure, which helps to achieve high specific capacity, excellent rate performance and good cycle stability of the final positive electrode material. In addition, this structure is also conducive to achieving sufficient carbon coating during the production process of the positive electrode material, further improving the performance of the material.
[0045] 3. Environmentally friendly, economical, and can be produced on a large scale commercially; the waste gas meets the emission standards after treatment, realizing clean production; further adding an exhaust gas treatment system allows the hydrochloric acid produced in the production process to be recycled and reused.
[0046] 4. Fast response speed, high production efficiency, short production process; stable condition control, stable product performance and low manufacturing cost.
[0047] The present invention also provides a method for preparing carbon-coated lithium manganese iron phosphate. The carbon-coated lithium manganese iron phosphate obtained by the present invention has excellent electrochemical properties as a positive electrode material for lithium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 is a schematic flow chart of a preparation method when the electrode active material is manganese iron oxide;
[0049] Figure 2 is a schematic flow chart of a preparation method when the electrode active material is ferromanganese pyrophosphate;
[0050] Figure 3 is a schematic flow chart of a preparation method when the electrode active material is lithium manganese iron phosphate;
[0051] Figure 4 is the XRD pattern of the ferromanganese oxide obtained in Example 1;
[0052] Figure 5 This is the SEM image of the ferromanganese oxide obtained in Example 1;
[0053] Figure 6 This is the XRD pattern of ferromanganese pyrophosphate obtained in Example 2;
[0054] Figure 7 This is a SEM image of the ferromanganese pyrophosphate obtained in Example 2;
[0055] Figure 8 This is the XRD pattern of lithium manganese iron phosphate obtained in Example 3;
[0056] Fig. 9 This is a SEM image of the lithium manganese iron phosphate obtained in Example 3;
[0057] Fig.10 This is the first discharge curve of the button-type battery assembled with carbon-coated lithium manganese iron phosphate obtained in Examples 4 to 6. DETAILED DESCRIPTION
[0058] The present invention provides a method for preparing an electrode active material, comprising the following steps:
[0059] mixing an iron source and a hydrochloric acid solution to obtain an iron source solution;
[0060] Mixing the iron source solution and the additive to obtain a mixed solution;
[0061] The mixed solution is sequentially subjected to atomization and high-temperature synthesis to obtain the electrode active material;
[0062] The additive includes additive 1, additive 2 or additive 3;
[0063] The additive 1 includes a manganese source;
[0064] The additive 2 includes a manganese source, phosphoric acid and a reducing agent;
[0065] The additive 3 includes a manganese source, a phosphorus source, a lithium source and a reducing agent.
[0066] The invention mixes the iron source and the hydrochloric acid solution to obtain the iron source solution.
[0067] In the present invention, the iron source preferably includes one or more of Fe, FeO, Fe2O3, Fe3O4, FeCl2, FeCl3, FeCO3, FeC2O4 and FeOOH.
[0068] In the present invention, the iron source solution contains H + The concentration is preferably 4 to 12 mol / L, specifically 4.5 mol / L, 5.5 mol / L or 8 mol / L; in terms of the amount of the substance of the iron element, the Fe element and H in the iron source solution are + The ratio of the amount of the substance is preferably 1: 2 to 8. In the present invention, the mixing is preferably carried out under stirring conditions.
[0069] In the present invention, the reaction occurring during the mixing of different iron sources is as follows:
[0070] Fe+2H + =Fe 2+ +H2↑
[0071] FeO+2H + =Fe 2+ +H2O
[0072] Fe2O3+6H + =2Fe 3+ +3H2O
[0073] Fe3O4+8H + =2Fe 3+ +Fe 2+ +4H2O
[0074] FeCO3+2H + =Fe 2+ +H2O+CO2↑
[0075] FeC2O4+2H + =Fe 2+ +H2C2O4
[0076] FeOOH+3H + =Fe 3+ +2H2O
[0077] After obtaining the iron source solution, the present invention mixes the iron source solution with an additive to obtain a mixed solution.
[0078] In the present invention, the additive includes additive 1, additive 2 or additive 3. In the present invention, the additive 1 includes a manganese source; the additive 2 includes a manganese source, phosphoric acid and a reducing agent; the additive 3 includes a manganese source, a phosphorus source, a lithium source and a reducing agent. In the present invention, the manganese source preferably includes one or more of Mn, MnO, MnCl2, MnCO3 and MnC2O4; the phosphorus source preferably includes one or more of phosphoric acid, lithium phosphate and lithium dihydrogen phosphate; the lithium source preferably includes one or more of lithium carbonate, lithium hydroxide, lithium chloride, lithium phosphate and lithium dihydrogen phosphate.
[0079] In the present invention, when the additive is additive 1, the concentration of manganese iron ions in the mixed solution is preferably 60 to 300 g / L, and more preferably 80 to 240 g / L; the manganese iron ions preferably include Mn 2+ , Fe 2+ and Fe 3+ ; Among them, Mn 2+ The amount of the substance of is preferably 0.1 to 1 and not 1, and more preferably 0.5 to 0.8 of the amount of the substance of manganese iron ions.
[0080] In the present invention, when the additive is additive 2, the concentration of manganese iron ions in the mixed solution is preferably 60 to 300 g / L, and more preferably 80 to 240 g / L; the manganese iron ions preferably include Mn 2+ and Fe 2+ ; Among them, Mn 2+The amount of substance preferably accounts for 0.1 to 1 of the amount of substance of manganese and iron ions, and is not 1, and is further preferably 0.5 to 0.8. In the present invention, the ratio of the total amount of substance of the manganese and iron ions to the amount of substance of the phosphorus element is preferably 0.95 to 1.0:1. In the present invention, the reducing agent preferably includes one or more of citric acid, oxalic acid, tartaric acid, formic acid and hydroxylamine hydrochloride; the mass of the reducing agent is preferably 1 to 5% of the mass of the electrode active material. In the present invention, when the additive is additive 2, the process of mixing the iron source solution and the additive is preferably: premixing the iron source solution, the manganese source and the reducing agent, and then adding phosphoric acid.
[0081] In the present invention, when the additive is additive 3, the concentration of manganese iron ions in the mixed solution is preferably 60 to 300 g / L, and more preferably 80 to 240 g / L; the manganese iron ions preferably include Mn 2+ and Fe 2+ ; Among them, Mn 2+ The amount of substance preferably accounts for 0.1 to 1 of the amount of substance of manganese iron ions, and is not 1, and is further preferably 0.5 to 0.8. In terms of the amount of substance of phosphorus element and lithium element, the ratio of the total amount of substance of manganese iron ions to the amount of substance of phosphorus element is preferably 0.95 to 1.0:1, and the ratio of the amount of substance of lithium element and phosphorus element is preferably 0.95 to 1.05:1. In the present invention, the type and amount of the reducing agent are consistent with those specified in the above technical solution, and will not be repeated here. In the present invention, when the additive is additive 3, the process of mixing the iron source solution and the additive is preferably: premixing the iron source solution, manganese source and reducing agent, and then adding the phosphorus source and lithium source.
[0082] In the present invention, the reaction that occurs when a manganese source is added to an iron source solution is as follows:
[0083] 2Fe 3+ +Mn=2Fe 2+ +Mn 2+
[0084] Mn+2H + =Mn 2+ +H2↑
[0085] MnO+2H + =Mn 2+ +H2O
[0086] MnCO3+2H + =Mn 2+ +H2O+CO2↑
[0087] MnC2O4+2H + =Mn 2++H2C2O4
[0088] After obtaining the mixed solution, the present invention sequentially performs atomization and high-temperature synthesis on the mixed solution to obtain the electrode active material.
[0089] Before the atomization, the present invention also preferably includes filtering the mixed liquid and then transferring it to an atomizer for atomization. In the present invention, the atomization method is preferably gas-liquid two-fluid atomization; when the additive is additive 1, the gas used for the atomization is preferably air or oxygen; when the additive is additive 2 or additive 3, the gas used for the atomization is preferably nitrogen; the gas pressure of the atomization is preferably 0.3-0.8MPa, and the average particle size of the mist droplets obtained by the atomization is preferably 10-100μm.
[0090] In the present invention, when the additive is additive 1, the temperature of the high temperature synthesis is preferably 500-1000°C, and the holding time is preferably 10-60s; when the additive is additive 2, the temperature of the high temperature synthesis is preferably 500-800°C, and the holding time is preferably 10-60s; when the additive is additive 3, the temperature of the high temperature synthesis is preferably 600-900°C, and the holding time is preferably 10-60s. In the present invention, the high temperature synthesis is preferably carried out in an atomized high temperature synthesis furnace, and the atomized high temperature synthesis furnace is heated by internal heat, that is, heated by a burner flame, and the heat source is a high temperature gas formed after the combustion of natural gas; when the additive is additive 1, the oxygen content in the high temperature gas is preferably 1%-10%; when the additive is additive 2 or additive 3, the oxygen content in the high temperature gas is preferably less than 1%.
[0091] In the present invention, when the additive is additive 1, the mist droplets are sequentially subjected to high-temperature drying and pyrolysis reactions during the high-temperature synthesis process to obtain solid powder and flue gas, and the reactions that occur are as follows:
[0092] 2Fe 3+ +6Cl - +3H2O=Fe2O3+6HCl↑
[0093] 4Fe 2+ +8Cl - +O2+4H2O=2Fe2O3+8HCl↑
[0094] 4Mn 2+ +8Cl - +O2+4H2O=2Mn2O3+8HCl↑
[0095] xMn2O3+(1-x)Fe2O3=(Mn x Fe 1-x )2O3
[0096] In the present invention, when the additive is additive 2 or additive 3, the mist droplets undergo high-temperature drying, precipitation reaction and condensation reaction in sequence during the high-temperature synthesis process to obtain solid powder and flue gas; the reducing agent decomposes and carbonizes at high temperature to consume oxygen in the flue gas, preventing the oxidation of ferrous ions, and the remaining trace carbon remains in the solid powder.
[0097] In the present invention, when the additive is additive 2, the reaction occurring during the high temperature synthesis process is as follows:
[0098] FeCl2+H3PO4=FeHPO4+2HCl↑
[0099] MnCl2+H3PO4=MnHPO4+2HCl↑
[0100] 2xMnHPO4+2(1-x)FeHPO4=(Mn x Fe 1-x )2P2O7+H2O↑
[0101] In the present invention, when the additive is additive 3, the phosphorus source is phosphoric acid, and the lithium source is lithium chloride, the reaction occurring during the high temperature synthesis process is as follows:
[0102] FeCl2+H3PO4=FeHPO4+HCl↑
[0103] MnCl2+H3PO4=MnHPO4+HCl↑
[0104] LiCl+xMnHPO4+(1-x)FeHPO4=LiMn x Fe 1-x PO4+HCl↑
[0105] In the present invention, solid powder and flue gas are preferably obtained after the high temperature synthesis. After obtaining the flue gas, the present invention also preferably includes post-processing the flue gas, and the post-processing preferably includes:
[0106] Separating the flue gas into gas and solid to obtain acid gas and solid particles;
[0107] Regenerating the acid gas with acid, and recycling the recovered acid back into the preparation process of the iron source solution for cyclic use;
[0108] The solid particles and solid powder are mixed and then crushed to obtain the electrode active material.
[0109] In the present invention, the crushing method preferably includes air flow crushing, mechanical crushing, dry ball milling or wet grinding.
[0110] The present invention also provides an electrode active material prepared by the preparation method described in the above technical solution. When the additive is additive 1, the electrode active material is recorded as electrode active material 1. The electrode active material 1 is manganese iron oxide. The chemical composition of the manganese iron oxide is (Mn x Fe 1-x )2O3, where 0.1≤x<1;
[0111] When the additive is additive 2, the electrode active material is recorded as electrode active material 2, the electrode active material 2 is ferromanganese pyrophosphate, and the chemical composition of the ferromanganese pyrophosphate is (Mn x Fe 1-x )2P2O7, where 0.1≤x<1;
[0112] When the additive is additive 3, the electrode active material is recorded as electrode active material 3, the electrode active material 3 is lithium iron manganese phosphate, and the chemical composition of the lithium iron manganese phosphate is LiMn x Fe 1-x PO4, where 0.1≤x<1;
[0113] The electrode active material has a porous structure.
[0114] In the present invention, the average particle size of the manganese iron oxide is preferably 2 to 10 μm, and the bulk density is preferably 0.6 to 1.2 g / cm 3 The tap density is preferably 1.0 to 2.0 g / cm 3 .
[0115] In the present invention, the average particle size of the ferromanganese pyrophosphate is preferably 2 to 10 μm, and the bulk density is preferably 0.2 to 0.4 g / cm 3 The tap density is preferably 0.4 to 0.8 g / cm 3 , the carbon content is preferably less than 0.2%.
[0116] In the present invention, the average particle size of the lithium manganese iron phosphate is preferably 2 to 10 μm, and the bulk density is preferably 0.2 to 0.6 g / cm 3 The tap density is preferably 0.5 to 1.0 g / cm 3 , the carbon content is preferably less than 0.5%.
[0117] In the present invention, the flow diagram of the preparation method when the electrode active material is manganese iron oxide is as follows Figure 1 As shown; the schematic diagram of the preparation method when the electrode active material is ferromanganese pyrophosphate is as shown Figure 2 As shown; the schematic diagram of the preparation method when the electrode active material is lithium manganese iron phosphate is as shown Figure 3 shown.
[0118] The present invention also provides a method for preparing carbon-coated lithium manganese iron phosphate, comprising the following steps:
[0119] Providing an electrode active material, wherein the electrode active material is the electrode active material described in the above technical solution;
[0120] Carbon-coating the electrode active material to obtain the carbon-coated lithium manganese iron phosphate;
[0121] When the electrode active material is the electrode active material 1, the carbon coating process is: mixing the electrode active material 1, lithium dihydrogen phosphate and a carbon source, and calcining;
[0122] When the electrode active material is electrode active material 2, the carbon coating process is: mixing electrode active material 2, a lithium source and a carbon source, and calcining; the lithium source includes lithium carbonate or lithium hydroxide;
[0123] When the electrode active material is the electrode active material 3, the carbon coating process is: mixing the electrode active material 3 and the carbon source, and calcining.
[0124] In the present invention, when the electrode active material is electrode active material 1 or electrode active material 2, the ratio of the total amount of manganese element and iron element to the amount of lithium element is preferably 1:1.00~1.05.
[0125] In the present invention, the carbon source preferably includes one or more of glucose, sucrose, soluble starch and polyethylene glycol. In the present invention, the mass percentage of the carbon coating layer on the carbon-coated lithium manganese iron phosphate is preferably 1.5-2.5%. In the present invention, the mixing method is preferably grinding mixing. In the present invention, the calcination temperature is preferably 500-900°C, more preferably 600-800°C; the insulation time is preferably 3-20h, more preferably 4-10h.
[0126] Unless otherwise specified, the materials and equipment used in the present invention are all commercially available products in the art.
[0127] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0128] Example 1
[0129] Add Fe2O3 to hydrochloric acid solution under stirring to obtain an iron source solution, in which H + The concentration of Fe and H is 8.0 mol / L. + The ratio of the amount of substance is 1:6.4;
[0130] MnCO3 was added to the iron source solution to obtain a mixed solution, in which the manganese and iron ion concentration was 230 g / L, Mn 2+ The amount of substances in manganese and iron ions accounts for 70%;
[0131] The obtained mixed liquid was filtered and then transferred to an atomizer to be atomized into mist droplets, wherein the gas used for atomization was air, the atomization pressure was 0.45 MPa, and the average particle size of the obtained mist liquid was 38 μm;
[0132] The obtained mist droplets are subjected to high temperature synthesis at 700° C. (wherein the oxygen content in the high temperature gas is 9%), and the temperature is kept for 25 seconds to obtain solid powder and flue gas; the flue gas is subjected to gas-solid separation to obtain acid gas and solid particles; the acid gas is subjected to acid regeneration, and the recovered acid is returned to the preparation process of the iron source solution for recycling; the solid particles and solid powder are mixed and crushed in a jet crusher to obtain manganese iron oxide (Mn 0.7 Fe 0.3 )2O3 powder, and its related physicochemical parameters are shown in Table 1.
[0133] Example 2
[0134] Add FeO to hydrochloric acid solution under stirring to obtain an iron source solution, wherein H + The concentration of Fe and H is 5.5 mol / L. + The ratio of the amount of substance is 1:5.5;
[0135] Mn and citric acid (mass fraction of electrode active material 4%) were added to the iron source solution and mixed evenly, and then phosphoric acid was added to obtain a mixed solution, in which the manganese and iron ion concentration was 158 g / L, Mn 2+ The amount of substance in manganese and iron ions accounts for 65%; the ratio of the total amount of manganese and iron ions to the amount of phosphorus is 0.98:1;
[0136] The obtained mixed liquid was filtered and then transferred to an atomizer to be atomized into mist droplets, wherein the atomization gas used was nitrogen gas, the atomization gas pressure was 0.50 MPa, and the average particle size of the obtained mist liquid was 29 μm;
[0137] The obtained mist droplets are subjected to high temperature synthesis at 680° C. (wherein the oxygen content in the high temperature gas is 0.2%), and the temperature is kept for 20 seconds to obtain solid powder and flue gas; the flue gas is subjected to gas-solid separation to obtain acid gas and solid particles; the acid gas is subjected to acid regeneration, and the recovered acid is returned to the preparation process of the iron source solution for recycling; the solid particles and solid powder are mixed and crushed in a mechanical crusher to obtain ferromanganese pyrophosphate (Mn 0.65 Fe 0.35 )2P2O7 powder, and its related physicochemical parameters are shown in Table 1.
[0138] Example 3
[0139] Add Fe into hydrochloric acid solution under stirring to obtain an iron source solution, wherein H + The concentration of Fe and H + The ratio of the amount of substance is 1:4.5;
[0140] Mn and oxalic acid (mass fraction of electrode active material 3%) were added to the iron source solution and mixed evenly, and then phosphoric acid and lithium chloride were added to obtain a mixed solution, in which the manganese and iron ion concentration was 138 g / L, Mn 2+ The amount of substance in manganese iron ions accounts for 60%; the ratio of the total amount of manganese iron ions to the amount of phosphorus is 0.99:1, and the ratio of the amount of lithium to phosphorus is 1.02:1;
[0141] The obtained mixed liquid was filtered and then transferred to an atomizer to be atomized into mist droplets, wherein the atomization gas used was nitrogen gas, the atomization gas pressure was 0.58 MPa, and the average particle size of the obtained mist liquid was 22 μm;
[0142] The obtained mist droplets are subjected to high temperature synthesis at 720°C (wherein the oxygen content in the high temperature gas is 0.15%), and kept warm for 30 seconds to obtain solid powder and flue gas; the flue gas is subjected to gas-solid separation to obtain acid gas and solid particles; the acid gas is subjected to acid regeneration, and the recovered acid is returned to the preparation process of the iron source solution for recycling; the solid particles and solid powder are mixed and crushed in an air flow crusher to obtain lithium manganese iron phosphate LiMn 0.6 Fe 0.4 PO4 powder, related physicochemical parameters are shown in Table 1.
[0143] Table 1 Physicochemical parameters of electrode active materials obtained in Example
[0144]
[0145] Example 4
[0146] 2000 g of manganese iron oxide obtained in Example 1, 2650.4 g of lithium dihydrogen phosphate, 160 g of polyethylene glycol and 500 g of anhydrous glucose were ground and mixed, wherein the ratio of the total amount of manganese element and iron element to the amount of lithium element was 1:1.01; the obtained mixture was calcined at 745°C and kept warm for 10 hours to obtain carbon-coated lithium manganese iron phosphate, and the relevant physicochemical parameters are shown in Table 2.
[0147] Example 5
[0148] 2000 g of ferromanganese pyrophosphate obtained in Example 2, 262 g of lithium carbonate, 50 g of polyethylene glycol and 160 g of anhydrous glucose were ground and mixed, wherein the ratio of the total amount of manganese element and iron element to the amount of lithium element was 1:1.01; the obtained mixture was calcined at 720°C and kept warm for 8 hours to obtain carbon-coated lithium manganese iron phosphate, and the relevant physicochemical parameters are shown in Table 2.
[0149] Example 6
[0150] 2000 g of lithium manganese iron phosphate obtained in Example 3, 40 g of polyethylene glycol and 120 g of anhydrous glucose were ground and mixed, and the obtained mixture was calcined at 700° C. and kept warm for 6 hours to obtain carbon-coated lithium manganese iron phosphate. The relevant physicochemical parameters are shown in Table 2.
[0151] Table 2 Physicochemical parameters of carbon-coated lithium manganese iron phosphate obtained in Example
[0152] Serial number Chemical formula C% Li% Mn% Fe% 0.1C first discharge capacity mAh / g Example 4 <![CDATA[LiMn 0.7 Fe 0.3 PO4 / C]]> 1.85 4.34 23.57 10.26 154.2 Example 5 <![CDATA[LiMn 0.65 Fe 0.35 PO4 / C]]> 1.91 4.35 21.84 11.95 157.4 Example 6 <![CDATA[LiMn 0.6 Fe 0.4 PO4 / C]]> 1.82 4.35 20.22 13.67 159.5
[0153] Performance Testing
[0154] Test Example 1
[0155] Figure 4 The manganese iron oxide (Mn 0.7 Fe 0.3 )2O3, it can be seen from the figure that the material synthesized in Example 1 is consistent with the standard card PDF#71-0637 corresponding to (Mn 0.37 Fe 0.63 )2O3 completely corresponds to each other, and there is no other impurity phase. It can be inferred that the sample in Example 1 forms a manganese-iron oxide solid solution. Figure 5 The SEM image of the ferromanganese oxide obtained in Example 1 is shown in FIG. Figure 5 It can be seen that the sample has a porous structure, the primary particle size is about 200-400nm, and the particle surface is smooth and round.
[0156] Figure 6 The manganese ferrophosphate (Mn) obtained in Example 2 0.65 Fe 0.35)XRD diagram of Mn2P2O7. It can be seen from the figure that the material synthesized in Example 2 completely corresponds to the Mn2P2O7 corresponding to the standard card PDF#77-1244, and there is no other impurity phase. It is inferred that the sample in Example 2 forms a manganese-iron pyrophosphate solid solution. Figure 7 This is the SEM image of the ferromanganese pyrophosphate obtained in Example 2. Figure 7 It can be seen that the sample has a porous structure, the primary particle size is small, about 100-200nm, and the particle surface is smooth and round, which is suitable for the preparation of high-performance carbon-coated lithium manganese iron phosphate positive electrode materials.
[0157] Figure 8 The lithium iron manganese phosphate LiMn obtained in Example 3 0.6 Fe 0.4 From the XRD diagram of PO4, it can be seen that the material synthesized in Example 3 is between LiMnPO4 corresponding to the standard card PDF#77-0178 and LiFePO4 corresponding to PDF#40-1499, without other impurities. It is inferred that the sample in Example 3 forms a lithium manganese iron phosphate solid solution. Fig. 9 This is the SEM image of the lithium manganese iron phosphate obtained in Example 3. Fig. 9 It can be seen that the sample has a porous structure, the primary particle size is about 200-400nm, and the particle surface is smooth and round. Because it is already pure lithium manganese iron phosphate, high-performance carbon-coated lithium manganese iron phosphate positive electrode material can be obtained by carbon coating after grinding.
[0158] Test Example 2
[0159] The carbon-coated lithium manganese iron phosphate positive electrode material prepared in Examples 4 to 6 was used to prepare a positive electrode sheet, and button batteries were assembled according to the standard of GB31241-2014. The electrochemical performance of the button battery was tested using a blue power test system (range I: 10 mA; range U: 5 V). The test voltage range was 2.5-4.5 V, and the first charge and discharge performance was tested at 0.1 C. Fig.10 The first discharge curves of the button cells assembled with the carbon-coated lithium manganese iron phosphate obtained in Examples 4 to 6 show that the 0.1C first discharge gram capacities of the carbon-coated lithium manganese iron phosphate positive electrode material prepared by the present method are 154.2 mAh / g, 157.4 mAh / g, and 159.5 mAh / g, respectively, which are higher than 150.8 mAh / g of a certain commercially available product comparison example.
[0160] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A method for preparing an electrode active material, characterized in that: The following steps are involved: mixing an iron source and a hydrochloric acid solution to obtain an iron source solution; Mixing the iron source solution and the additive to obtain a mixed solution; The mixed solution is sequentially subjected to atomization and high-temperature synthesis to obtain the electrode active material; The additive includes additive 1, additive 2 or additive 3; The additive 1 includes a manganese source; The additive 2 includes a manganese source, phosphoric acid and a reducing agent; The additive 3 includes a manganese source, a phosphorus source, a lithium source and a reducing agent.
2. The preparation method according to claim 1, characterized in that: The iron source includes one or more of Fe, FeO, Fe2O3, Fe3O4, FeCl2, FeCl3, FeCO3, FeC2O4 and FeOOH; The iron source solution contains H + The concentration is 4-12 mol / L; In terms of the amount of iron, the Fe element and H in the iron source solution + The amount of substance ratio is 1:2~8.
3. The preparation method according to claim 2, characterized in that: The manganese source includes one or more of Mn, MnO, MnCl2, MnCO3 and MnC2O4; The phosphorus source includes one or more of phosphoric acid, lithium phosphate and lithium dihydrogen phosphate; The lithium source includes one or more of lithium carbonate, lithium hydroxide, lithium chloride, lithium phosphate and lithium dihydrogen phosphate.
4. The preparation method according to claim 3, characterized in that: When the additive is additive 1, the concentration of manganese and iron ions in the mixed solution is 60-300 g / L, wherein Mn 2+ The amount of substance of accounts for 0.1 to 1 of the amount of substance of manganese and iron ions, and is not 1; When the additive is additive 2, the concentration of manganese and iron ions in the mixed solution is 60-300 g / L; 2+ The amount of substance of accounts for 0.1 to 1 of the amount of substance of manganese and iron ions, and is not 1; based on the amount of substance of phosphorus element, the ratio of the total amount of substance of manganese and iron ions to the amount of substance of phosphorus element is 0.95 to 1.0:1; When the additive is additive 3, the concentration of manganese and iron ions in the mixed solution is 60-300 g / L; 2+ The amount of substance accounts for 0.1 to 1 of the amount of substance of manganese iron ions, and is not 1; based on the amount of substance of phosphorus element and lithium element, the ratio of the total amount of manganese iron ions to the amount of substance of phosphorus element is 0.95 to 1.0:1, and the ratio of the amount of substance of lithium element and phosphorus element is 0.95 to 1.05:
1.
5. The preparation method according to claim 4, characterized in that: The reducing agent includes one or more of citric acid, oxalic acid, tartaric acid, formic acid and hydroxylamine hydrochloride; The mass of the reducing agent is 1-5% of the mass of the electrode active material.
6. The preparation method according to claim 1, characterized in that: The atomization method is gas-liquid two-fluid atomization; the gas pressure of the atomization is 0.3-0.8 MPa, and the average particle size of the mist droplets obtained by the atomization is 10-100 μm.
7. The preparation method according to claim 1, characterized in that: When the additive is additive 1, the temperature of the high temperature synthesis is 500 to 1000° C., and the holding time is 10 to 60 seconds; When the additive is additive 2, the temperature of the high temperature synthesis is 500 to 800° C., and the holding time is 10 to 60 seconds; When the additive is additive 3, the temperature of the high temperature synthesis is 600-900° C., and the holding time is 10-60 seconds.
8. The electrode active material prepared by the preparation method according to any one of claims 1 to 7, characterized in that: When the additive is additive 1, the electrode active material is recorded as electrode active material 1, the electrode active material 1 is manganese iron oxide, and the chemical composition of the manganese iron oxide is (Mn x Fe 1-x )2O3, where 0.1≤x<1; When the additive is additive 2, the electrode active material is recorded as electrode active material 2, the electrode active material 2 is ferromanganese pyrophosphate, and the chemical composition of the ferromanganese pyrophosphate is (Mn x Fe 1-x )2P2O7, where 0.1≤x<1; When the additive is additive 3, the electrode active material is recorded as electrode active material 3, the electrode active material 3 is lithium iron manganese phosphate, and the chemical composition of the lithium iron manganese phosphate is LiMn x Fe 1-x PO4, where 0.1≤x<1; The electrode active material has a porous structure.
9. A method for preparing carbon-coated lithium manganese iron phosphate, characterized in that: The following steps are involved: Providing an electrode active material, wherein the electrode active material is the electrode active material according to claim 8; Carbon-coating the electrode active material to obtain the carbon-coated lithium manganese iron phosphate; When the electrode active material is the electrode active material 1, the carbon coating process is: mixing the electrode active material 1, lithium dihydrogen phosphate and a carbon source, and calcining; When the electrode active material is electrode active material 2, the carbon coating process is: mixing electrode active material 2, a lithium source and a carbon source, and calcining; the lithium source includes lithium carbonate or lithium hydroxide; When the electrode active material is the electrode active material 3, the carbon coating process is: mixing the electrode active material 3 and the carbon source, and calcining.
10. The preparation method according to claim 9, characterized in that: The calcination temperature is 500-900° C., and the heat preservation time is 3-20 hours.
Citation Information
Patent Citations
Preparation method of lithium manganese ferric phosphate anode material
CN104934601A
Preparation method of spherical lithium manganese iron phosphate with high tap density
CN115180608A
Lithium manganese iron phosphate positive electrode material and preparation method thereof
CN115535993A
Carbon-coated lithium manganese iron phosphate material, preparation method thereof and battery
CN115744860A
Lithium manganese iron phosphate positive electrode material and preparation method thereof
CN115849327A
Cited By
Method for regulating and controlling highly exposed {010} crystal face of manganese-rich phosphate-based positive electrode material
CN122010076A